(untitled) (Journal of the College of Basic Education, 2023)
The issue of time has not received its share of attention in studies and research.Geographical, especially at the country level, despite the importance of time in human activities and life on earth. for thisThe indicator has deep implications and implications that increase understanding and understanding of the nature of the relationship of individuals to the land throughOrganizing daily events and activities that are affected by economic, social, cultural and political indicators.Time can be considered a natural resource in human life, the outcome of which is positive in the case ofInvesting it in carrying out activities in an organized manner. On the contrary, there will be a waste of timeIt is not redeemable during the life of the individual.This research aims to show the importance of time from a geographical point of view and to reveal the relationship of its distribution and organization.According to the life indicators of the families, according to the hypothesis of its content, that the organization and harmony of the daily time distribution inAchievement and satisfaction of daily activities for urban families is linked to certain variables and has important implications.in life